Comparative Study of Analgesic and Haemodynamic Spectrum Of 0.5% Ropivacaine Vs 0.5% Levobupivacaine in Ultrasonography Guided Supraclavicular Brachial Plexus Block - Yogini Ramdas Adhau; Benhur Premendran; Pradeep Dhande; Sucheta Tidke, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Regional anesthesia via peripheral nerve blocks is widely used for providing effective intraoperative and postoperative analgesia in upper limb surgeries. The supraclavicular brachial plexus block offers reliable anesthesia for such procedures. Newer local anesthetics such as levobupivacaine and ropivacaine have been introduced to reduce cardiotoxicity concerns associated with bupivacaine while maintaining efficacy. This study aims to compare the analgesic efficacy and hemodynamic effects of 0.5% levobupivacaine versus 0.5% ropivacaine in ultrasound-guided supraclavicular brachial plexus blocks. Methods: A prospective, randomized, double-blind comparative study was conducted on 60 ASA grade I and II patients aged 20–60 years undergoing elective upper limb surgery. Patients were randomized into two groups: Group L received 0.5% levobupivacaine, and Group R received 0.5% ropivacaine via ultrasound-guided supraclavicular brachial plexus block. The onset and duration of sensory and motor blockade, time to first rescue analgesia, and intraoperative hemodynamic parameters (heart rate, blood pressure, oxygen saturation) were recorded and analyzed. Results: Group L (levobupivacaine) demonstrated significantly earlier onset of sensory (11.13 ± 1.00 min) and motor blockade (13.20 ± 1.12 min) compared to Group R (ropivacaine) with sensory onset of 13.60 ± 0.81 min and motor onset of 15.60 ± 0.81 min (p=0.0001). Duration of both sensory and motor blockade was longer in Group L. Time to first rescue analgesia was also significantly prolonged in Group L (11.80 ± 0.40 hours) versus Group R (10.20 ± 0.55 hours) (p=0.0001). Hemodynamic parameters remained stable and comparable between groups throughout the study with no significant adverse events. Conclusions: 0.5% levobupivacaine provides faster onset, longer duration of sensory and motor blockade, and prolonged postoperative analgesia compared to 0.5% ropivacaine in ultrasound-guided supraclavicular brachial plexus block, without significant hemodynamic compromise. Levobupivacaine is thus an effective and safe option for upper limb regional anesthesia.